2012
DOI: 10.1074/jbc.m111.287128
|View full text |Cite
|
Sign up to set email alerts
|

SATB Homeobox Proteins Regulate Trophoblast Stem Cell Renewal and Differentiation

Abstract: Background: Trophoblast cells, the functional components of the placenta, are derived from multipotent trophoblast stem (TS) cells. Results: SATB homeobox proteins regulate the TS cell stem state through up-regulation of a stem-specific transcription factor, EOMES, and inhibition of trophoblast differentiation. Conclusion: SATB proteins regulate TS cell development. Significance: Understanding TS cell biology is crucial to determining processes underlying placental development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 69 publications
4
69
0
Order By: Relevance
“…For example, the chromatin organizers SATB homeobox 1 (SATB1) and SATB2 have been shown to be essential for maintaining a stem-cell identity within rat TSCs (Asanoma, et al 2012). Mechanistic analyses showed that loss of SATB proteins in TSCs resulted in reduced expression of Eomes and loss of TSC self-renewal.…”
Section: Chromatin Remodeling Factors and Trophoblast Developmentmentioning
confidence: 99%
“…For example, the chromatin organizers SATB homeobox 1 (SATB1) and SATB2 have been shown to be essential for maintaining a stem-cell identity within rat TSCs (Asanoma, et al 2012). Mechanistic analyses showed that loss of SATB proteins in TSCs resulted in reduced expression of Eomes and loss of TSC self-renewal.…”
Section: Chromatin Remodeling Factors and Trophoblast Developmentmentioning
confidence: 99%
“…Double-stranded small interfering RNA (siRNA) for SP1 (siSP1) (sc-29487) was purchased with control siRNA (sc-37007) from Santa Cruz Biotechnology. We also established HHUA cells with the stable knockdown of BHLHE40 and BHLHE41 by a lentivirus system (36). The transduced cells were selected by puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…An electrophoretic mobility shift assay (EMSA) was performed using nuclear extracts from 293T cells expressing HA-BHLHE40 and/or FLAG-BHLHE41 as described elsewhere (36). The sequences of the probes used are as follows: pTWIST1-wtSP1BS, 5=-CCGTCCCCTCCCC CTCCCGCCTCCCTCCCCGCCTCCCC-3=; pTWIST1-mtSP1BS, 5=-CC GTCCACTACACATCACGCATACATACACGACTCCCC-3=.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations